2020
DOI: 10.3390/foods9091259
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aqueous Chlorine Dioxide in Minimizing Food Safety Risk Associated with Salmonella, E. coli O157:H7, and Listeria monocytogenes on Sweet Potatoes

Abstract: Sodium hypochlorite (NaOCl) is a commonly used sanitizer in the produce industry despite its limited effectiveness against contaminated human pathogens in fresh produce. Aqueous chlorine dioxide (ClO₂) is an alternative sanitizer offering a greater oxidizing potency with greater efficacy in reducing a large number of microorganisms. We investigated the effect of aqueous chlorine dioxide treatment against human pathogens, Salmonella, Escherichia coli O157:H7, and Listeria monocytogenes seeded on sweet potatoes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Chlorine compounds are widely used as sanitizing agents in the food industry and drinkable water treatments. Several studies have shown the inactivation effects of such chlorine compounds on L. monocytogenes [ 54 , 55 ]. The lethal effect could be explained by membrane damage leading to a loss of permeability control [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chlorine compounds are widely used as sanitizing agents in the food industry and drinkable water treatments. Several studies have shown the inactivation effects of such chlorine compounds on L. monocytogenes [ 54 , 55 ]. The lethal effect could be explained by membrane damage leading to a loss of permeability control [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Food is the material basis for human survival ( Polychronou et al, 2020 ). Food security refers to the fact that everyone can buy and afford the food they need without being affected by time and space ( Luu et al, 2020 ). The food must not cause any harm to the human body first, and secondly it can satisfy the nutritional needs ( Vikram et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Chlorine dioxide is a strong oxidant with an antimicrobial activity that is often recommended for use as a disinfectant, even at low concentrations, to kill microorganisms [ 2 , 3 , 4 ]. As such, chlorine dioxide is a broad-spectrum [ 5 ], safe, and efficient disinfectant [ 6 , 7 ] due to its high oxidation efficiency and its ability to reduce the formation of organic chlorination by-products during the application, and has been used in a wide range of applications including disinfection of water [ 8 ] and wastewater [ 9 ], medical devices [ 10 , 11 ], agricultural products [ 12 , 13 , 14 ], and Stomatology [ 15 ].…”
Section: Introductionmentioning
confidence: 99%